The dynamics of corporate social responsibility : a critical approach to theory and practice - Aluchna, Maria; Idowu, Samuel O. (Springer, 2017)
This book explores recent developments in the theory, strategic perspective and international practice of corporate social responsibility. In particular it discusses the consequences of the economic slowdown apparent in many economies and the impact of changes in the regulatory environment. It consists of three parts: Part one addresses a variety of theoretical approaches as well as the dynamics and criticism of corporate social responsibility. It takes into account social and governmental expectations for the new and extended role of companies in the economy and in society, and provides a new context and theoretical assumptions regarding the functions and tasks of corporate social responsibility. Part two discusses the practical aspects relating to strategic management and corporate governance, corporate disclosure and reporting, as well as the empowerment of stakeholders. Lastly, part three focuses on the international practice of corporate social responsibility in various organizational and institutional settings. Using numerous case studies, the book explores the challenges and tasks of CSR in emerging markets, in the fashion industry and in global and family companies. It identifies the changes that can be detected following the financial crisis, closing the loop and linking the empirical findings with the revised theoretical framework.
Keywords: Social responsibility of business.; Business ethics.; Corporate governance -- Moral and ethical aspects.; Industrial management -- Environmental aspects.; elektronické knihy; electronic books